The benefit of the doubt: Willful ignorance and altruistic punishment - Robert Stüber (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
Altruistic punishment is often thought to be a major enforcement mechanism of social norms. I present experimental results from a modified version of the dictator game with third-party punishment, in which third parties can remain ignorant about the choice of the dictator. I find that a substantial fraction of subjects choose not to reveal the dictator's choice and not to punish the dictator. I show that this behavior is in line with the social norms that prevail in a situation of initial ignorance. Remaining ignorant and choosing not to punish is not inappropriate. As a result, altruistic punishment is significantly lower when the dictator's choice is initially hidden. The decrease in altruistic punishment leads to more selfish dictator behavior only if dictators are explicitly informed about the effect of willful ignorance on punishment rates. Hence, in scenarios in which third parties can ignore information and dictators know what this implies, third-party punishment may only ineffectively enforce social norms.
Keywords: C91; D01; D63; D83; 330; Third-party punishment; Willful ignorance; Sorting; Social preference